O lugar destinado ao negro liberto na sociedade branca do século XIX - Jacinto, Claudia Graziolli Somma (2007)
The coffee s culture brought to the Province of São Paulo a significant growth in the fields economic, social, and politician. In a context of fast transformation and transistion of enslaved man power for wage-earner, the slave who soon would receive its freedom and that he knew its place in this social context, it starts to occupy bordering places taxes for the elite s coffee in growth. The end of century XIX (1871 at 1890) corresponds to the period studied in this work and argues practical legal the relative ones to the emancipation of the slaves before the Golden Law, the procedures segregacionistas that if reveal in the actions of entities, of the orphans judges, in the mind of ethnic cleanness, the scientific said practical conceptions